Pilgrimage toward a Common Vision of the Church - Wondra, Ellen K. (The ecumenical review, 2022)
In 2013, the World Council of Churches (WCC) published its second convergence statement, The Church: Towards a Common Vision (TCTCV), and invited churches, ecumenical councils and groups, and others to respond officially with their assessment of the extent to which convergence had been reached in many areas. After offering an outline of the process in the WCC and its Commission on Faith and Order that led to this statement, this article discusses the process of evaluating the responses to the document and the main issues that were raised in the responses. The article notes the uneven nature of the responses in that no responses were received from Latin America or Africa and very few responses came from Pentecostal, evangelical, charismatic, or independent churches and movements. The article concludes by affirming the need for changes in the methodology of Faith and Order to more readily and clearly hear those churches and peoples who have long and often been marginalized.